To solve the equation \( 3(-7x - 6) = -2(x - 6) \), we will start by distributing both sides.
-
Distribute \( 3 \) on the left side: \[ 3(-7x) + 3(-6) = -21x - 18 \]
-
Distribute \( -2 \) on the right side: \[ -2(x) + 2(6) = -2x + 12 \]
Now, we can rewrite the equation: \[ -21x - 18 = -2x + 12 \]
Next, we will isolate \( x \). Start by adding \( 21x \) to both sides: \[ -18 = 21x - 2x + 12 \] This simplifies to: \[ -18 = 19x + 12 \]
Next, subtract \( 12 \) from both sides: \[ -18 - 12 = 19x \] This simplifies to: \[ -30 = 19x \]
Now, divide both sides by \( 19 \): \[ x = \frac{-30}{19} \]
Thus, the solution in simplest form is: \[ \boxed{\frac{-30}{19}} \]